Measurements of W+W− production cross-sections in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Rassloff, Damir Fabrice; Sauer, Christof; Schöning, André; Schultz-Coulon, Hans-Christian; et al. (Journal of high energy physics, 2025)
Measurements of W+W− → e±νμ∓ν production cross-sections are presented, providing a test of the predictions of perturbative quantum chromodynamics and the electroweak theory. The measurements are based on data from pp collisions at $$ \sqrt{s} $$= 13 TeV recorded by the ATLAS detector at the Large Hadron Collider in 2015-2018, corresponding to an integrated luminosity of 140 fb−1. The number of events due to top-quark pair production, the largest background, is reduced by rejecting events containing jets with b-hadron decays. An improved methodology for estimating the remaining top-quark background enables a precise measurement of W+W− cross-sections with no additional requirements on jets. The fiducial W+W− cross-section is determined in a maximum-likelihood fit with an uncertainty of 3.1%. The measurement is extrapolated to the full phase space, resulting in a total W+W− cross-section of 127 ± 4 pb. Differential cross-sections are measured as a function of twelve observables that comprehensively describe the kinematics of W+W− events. The measurements are compared with state-of-the-art theory calculations and excellent agreement with predictions is observed. A charge asymmetry in the lepton rapidity is observed as a function of the dilepton invariant mass, in agreement with the Standard Model expectation. A CP-odd observable is measured to be consistent with no CP violation. Limits on Standard Model effective field theory Wilson coefficients in the Warsaw basis are obtained from the differential cross-sections.
Veröffentlicht: 19. August 2025
*The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, D.F. Rassloff, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, L. Vigani, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Im Titel sind das Plus- und das Minuszeichen hochgestellt
Gesehen am 23.02.2026